Defining an intra-operative blunt mesenteric injury grading system and its use as a tool for surgical-decision making. Issue 1 (January 2019) - Bekker, Wanda; Hernandez, Matthew C.; Zielinski, Martin D.; Kong, Victor Y.; Laing, Grant L.; Bruce, John L.; Manchev, Vassil; Smith, Michelle T.D.; Clarke, Damian L.
Abstract: Background: The mesentery may be injured in trauma and few grading systems describe mesenteric injury severity. We aimed to develop and validate an intra-operative mesenteric injury grading system. Methods: A modified Delphi technique was used to generate an intraoperative grading system for blunt mesenteric injury called the mesenteric injury score (MIS). We performed a retrospective review (2010–2016) of patients >15 years old with blunt abdominal trauma. Patient demographics, injury severity score (ISS) and mechanism, clinical, operative, and outcome data were abstracted. The intraoperative grading system was used to describe patient outcomes including duration of stay and management approach. We compared the correlation of abdominal abbreviated injury score, Blunt Injury Prediction Score (BIPS) and the MIS with clinical outcomes using Spearman's rho. Results: There were fifty-one patients of which 86% were male. Injury mechanisms included motor vehicle accidents (n = 37, 73%), pedestrian vehicle accidents (n = 7, 13%), assaults (n = 4, 8%), falls (n = 2, 4%), and a single airplane crash (2%). Median [IQR] ISS was 16 [10–25] and GCS at hospital admission was 15 [15–15]. The median [IQR] international normalized ratio was 1.2 [1.1–1.5], lactate was 2.7 [1.7–4.9], and hemoglobin was 11.4 [8.6–12.2]. The distributions of MIS included Grade I (3, 5%), Grade II (10, 20%), Grade III (10, 20%), Grade IV, 5 (10%), and Grade V (23, 45%). Increasing mesenteric injury grade was associated with longer duration of stay, need for bowel resection, and damage control laparotomy. Conclusions: We developed an intra-operative mesenteric injury grading system (MIS) and provided an initial retrospective validation using a series of patients with blunt abdominal trauma. The proposed MIS corresponded with both the AIS and the BIPS. Future study comparing cross sectional imaging and operative findings based on MIS criteria is needed.